2012
DOI: 10.1177/1071181312561356
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Speed Perception in Virtual Environments Through Training

Abstract: The objective of this study is to determine the extent to which training can improve the speed perception of drivers in simulated environments. Seventy-two participants completed one of two driving simulator studies involving following a lead vehicle travelling at an unknown speed. Twenty-four subjects completed a training exercise to provide feedback at various speeds. The drivers who completed these short training exercises provided significantly better speed estimates without the aid of the speedometer duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Crucial to the success of both cognitive-based approaches is receiving timely feedback about performance, namely because it helps to accurately appraise the situation (Hattie & Timperley, 2007). In terms of speed management, feedback can lead to speed reduction (Oei & Polak, 1992) and better speed perception (Hill & Salzman, 2012); hence a powerful method for enhancing learning (Kluger & DeNisi, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Crucial to the success of both cognitive-based approaches is receiving timely feedback about performance, namely because it helps to accurately appraise the situation (Hattie & Timperley, 2007). In terms of speed management, feedback can lead to speed reduction (Oei & Polak, 1992) and better speed perception (Hill & Salzman, 2012); hence a powerful method for enhancing learning (Kluger & DeNisi, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Note that not only inclusion of functions (such as navigation, 3D view etc) for surgery, but also incorporating these functions systematically into interface design by considering the surgeon's requirements is an essential issue. Thus, recently, a user-centered virtual liver surgery planning system for liver surgery called Dr. Liver, has been developed, that considers human factors research, usability and time efficiency issues [3]. Human factors research describes how much and what kind of information a person can use effectively, and how information should be organized and presented to make it usable [4].…”
Section: Introductionmentioning
confidence: 99%
“…Feedback is another such training method which involves providing specific, non-biased information about one's actions, in order to facilitate a more accurate assessment of a given situation, ultimately providing more complete and representative knowledge (Molloy et al, 2018b). Study conducted by Hill and Salzman (2012) has indicated that in a road environment, feedback can effectively improve important skills such as speed perception, and speed estimation.…”
Section: Introductionmentioning
confidence: 99%